Ochronotic arthropathy: Report of case and review of the literature - Villegas González, Mauricio; García Sarmiento, Carlos; Galván-Villamarín, Fernando; Medina Castiblanco, Claudia (Revista Colombiana de Ortopedia y Traumatología, 2013)
Alkaptonuria is a hereditary disease that can be associated with homogentisic acid accumulation and cartilage weakening (ochronotic arthropathy). The case is presented of an 82 year-old male who showed an acute destruction of the hip joints, knees and shoulders. He received a total hip arthroplasty on his right side in 1992, and was not diagnosed with ochronosis. In 2007 he was diagnosed with hypertension, prostatism and cardiac valvulopathy, with macular degeneration, degenerative disc disease and cervical spondylarthrosis, also being present. The patient underwent multiple clinical, radiological, and pathological studies, which showed acute destructive arthropathy with morphological fragility of the cartilage, fibrosis, and dark pigmentation of the bone and cartilage. He was finally diagnosed with ochronotic arthropathy in 2010. Due to the low prevalence of this condition in our environment, which also reflects the difficulties in achieving a successful approach to a proper diagnosis and treatment, the orthopedic surgeon should have a high level of clinical suspicion provided by the knowledge of the existence of this disease.